(untitled) (New York, NY./London, England, 2005)
Although Japanese economic development is often discussed, less attention is given to social development, and much less to gender related issues. By examining Japanese experiences related to gender, the authors seek insights relevant to the current developing countries. Simultaneously, the book points out the importance for Japanese society to draw lessons from the creativity and activism of women in developing countries.
Keywords: Women,Women,Women in development; Social conditions,Economic conditions,Developing countries; 20th century.,20th century; Japan,Japan